RESPON STRUKTUR BETON GEDUNG APARTEMEN DAN PERKANTORAN 20 LANTAI AKIBAT BEBAN GEMPA DENGAN MENGGUNAKAN METODE RESPON SPEKTRUM - Kusbiantoro, Arief; Kusumawardani, Rini; Nugroho, Untoro; Sutarto, Agung; Dzikri, Muhammad Aidhil; Nugraha, Moh Ari Restian; Yus, Rakha Alfarizhi; Indonesia, Bisma Garda; Furqon, Septindra Hafizh Al; Firdaus, Nisqiyah; Khanza, Mirara (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2024)
A 20-story building located in Bandung, with a height of 70.5 m, functions as both an office building and an apartment complex. As a high-rise structure, seismic analysis of the building is required to determine the seismic pattern using the response spectrum method. The response spectrum method is used to compare V-static with Vdynamic based on SNI 1726-2019, and to determine the structural performance of the 20-story building frame. The results obtained for each frame using a combination of cases (static + seismic) show that, for displacement review, the highest shift occurs on the 20th floor at 1003.27 mm, and the highest drift value is on the 9th floor at 125.92 mm. The internal forces on the sample column show the highest results on the 5th-floor column C1 with 1.07x105 kN for Fx, 1.95x103 kN for Fy, and a moment of 5.44x103 kN-m, through the combination (static + seismic). Meanwhile, for the reviewed beam forces, the highest values are found on beam B53 on the 6th floor with an Fx value of 80.23 kN, Fy of 3140.53 kN, and the largest moment on the 15th-floor beam B53 of 793.46 kN-m.